2015
DOI: 10.1117/1.jmm.14.2.023502
|View full text |Cite
|
Sign up to set email alerts
|

Sub-10-nm patterning process using directed self-assembly with high χ block copolymers

Abstract: Abstract. The perpendicularly orientated lamellar structure of the self-organized diblock copolymer is an attractive template for sub-10-nm line-and-space pattern formation. We propose a method of evaluating the neutral layer (NL) whose performance has an important bearing on the perpendicular orientation of the lamellar structure. The random copolymer of methyl methacrylate and i-butyl POSS methacrylate (MAIBPOSS) has been investigated as an NL for a polymethylmethacrylate-b-polymethacrylethylPOSS (PMMA-b-PMA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…7,153−155 The International Technology Roadmap has specified a key metric for directed self-assembly: the defectivity of a nanopattern must be less than 0.01 cm −2 , which is orders of magnitude below the state-of-the-art. 7,20 Research to optimize the annealing of thin films of block copolymers is therefore critical. With respect to solvent vapor annealing, it has been reported that the rate of swelling, degree of swelling, annealing time, and deswelling rate all influence the resulting defect density.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…7,153−155 The International Technology Roadmap has specified a key metric for directed self-assembly: the defectivity of a nanopattern must be less than 0.01 cm −2 , which is orders of magnitude below the state-of-the-art. 7,20 Research to optimize the annealing of thin films of block copolymers is therefore critical. With respect to solvent vapor annealing, it has been reported that the rate of swelling, degree of swelling, annealing time, and deswelling rate all influence the resulting defect density.…”
Section: Chemistry Of Materialsmentioning
confidence: 99%
“…For semiconductor device applications, control over and quantification of the resulting defect density of a nanopattern is critical. , The International Technology Roadmap has specified a key metric for directed self-assembly: the defectivity of a nanopattern must be less than 0.01 cm –2 , which is orders of magnitude below the state-of-the-art. , Research to optimize the annealing of thin films of block copolymers is therefore critical. With respect to solvent vapor annealing, it has been reported that the rate of swelling, degree of swelling, annealing time, and deswelling rate all influence the resulting defect density. ,,,,, In terms of quantifying the defect density of a nanopattern formed via the self-assembly of a block copolymer, a well-described and automated method that extracts statistically relevant data would be preferred.…”
Section: Solvent Vapor Annealing and Defect Densitymentioning
confidence: 99%
See 1 more Smart Citation
“…This imbalance results in a preference of one block to wet the air interface, which results in formation of parallel orientations of lamella and either featureless surfaces or island/hole morphologies rather than the desired, uniformly thick perpendicular lamella needed for patterning (Figure 1). 39,40 Polystyrene-block-poly(2-vinylpyridine) (PS-b-P2VP) is a good representative of a high χ BCP demonstrating this behavior. PS and P2VP have a large difference in surface tension, γ, with γ PS = 27.9 mN/m and γ P2VP = 34.1 mN/m estimated at 200 °C, 41 and consequently, thin films on substrates treated with neutral brushes display lamellae with undesirable parallel orientations after thermal annealing.…”
mentioning
confidence: 99%
“…The χ value also affects the interfacial width between two domains. Higher χ usually results in a smaller interfacial width and decreases line-edge roughness [26,27]. Two broad types of high χ BCPs have been extensively explored: BCPs containing inorganic blocks and fully organic BCPs.…”
Section: Emerging High χ Bcpsmentioning
confidence: 99%